Nonmosaic 45, XO karyotype in a woman with Turner syndrome without any cognitive, psychosocial or behavioral deficiencies (A Case report) - Enny S Pamuji Djaswadi Dasuki (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2007)
A 22 year old woman with primary amenorrhea came to The Reproductive Endocrinology and Infertility Centre, University of Gadjah Mada, Dr.Sardjito Hospital. She had no abnormalities in cognitive, psychosocial or behavioral capacities, she had almost completed her university degree. On examination she had no secondary sexual development, no pathognomonic abnormal phenotype related to abnormal karyotype. There was no indication of family history associated ,;pecifically to the abnormal karyotype, phenotype feature of Turner syndrome and a specificThe patient karyotype analysis of blood sampling indicated 45XO, and it failed to demonstrate any mosaicism. Laparoscopic examination revealed a hypoplastic-lobulated-unicorns uterus, as streak gonad at the left side and no ovary at the other side.Keywords: Turner syndrome, non behavioral deficiencies. nonmosaic 45, XO karyotype, normal hormone level